Brand Identity "Baker Lab" Usaha Kue Rumahan - Axel Gema Ramadhan; M Nasrul Kamal (DEKAVE : Jurnal Desain Komunikasi Visual, 2022)
Baker Lab's visual indentity design is to design a logo as an identity that aims to determine visual elements that are different from other competitors to get a distinctive Baker Lab image in the eyes of the target audience, designing several supporting media such as posters, roll-banners, business cards, stickers, T-shirts, tumblers. This design uses the glass box method. Data collection uses primary data in the form of field observations, interviews and secondary data in the form of documentation, literature. The methods of data analysis in this work are strengths, weaknesses , opportunities and threats . The creative approach in the design of Baker Lab's visual identity is geographical, demographic, psychographic, creative objectives and creative programs. The main media used as an identity for the design of this visual identity is the Baker Lab logo while the supporting media are posters, roll-banners, business cards, stickers, T-shirts and tote bags. The formation of Baker Lab's visual identity, aligned with the target audience you want to aim for, so that the media design chosen is right on target. In the process of designing the Baker Lab, the author considered a lot of shapes, colors, as well as typography. The selection of logogram shapes inspired by the shape of houses, smoke and cakes goes through the stages of sketching and becoming a logogram. The logotype uses the Cooper Black font, the logotype design uses a type of font that gives a simple, and firm impression. The choice of orange for baker lab's identity gives the impression of warmth, creativity, and happiness, and chocolate symbolizes the color of a cake that is safe, comfortable and warm. Baker Lab's visual identity is applied to the main media including the Book Guideline as well as supporting media such as Posters, Roll Banners, Business Cards, Tote Bags, Stickers, and T-shirts.